Multidisciplinary team clinic for vocal cord dysfunction directs therapy and significantly reduces healthcare utilization. Issue 8 (18th March 2019) - Baxter, Malcolm; Ruane, Laurence; Phyland, Debra; Leahy, Elizabeth; Heke, Emily; Lau, Kenneth K.; Low, Kathy; Hamza, Kais; MacDonald, Martin; Bardin, Philip G.
ABSTRACT: Background and objective: Multidisciplinary team (MDT) clinics use an integrated approach to individualize care of complex medical conditions. Vocal cord dysfunction (VCD) is a challenging condition that is likely to benefit from MDT clinics but this has not been researched. Methods: A prospective observational cohort study of a novel VCD MDT clinic was conducted in patients with suspected VCD. Relevant questionnaires, medical history, physical examination, spirometry, dynamic computerized tomography (CT) larynx and laryngoscopy were utilized and patients were allocated to treatment pathways depending on putative diagnosis. Speech pathology intervention with laryngeal retraining (LR) was offered and if LR therapy failed botulinum toxin injection was offered. Primary outcome was reductions in healthcare utilization. Results: Overall, 80 consecutive patients were included in analyses. A definitive diagnosis of VCD was made in 56 of 80 (70%) patients. After LR ( n = 35), emergency department (ED)/hospital admissions declined significantly in the subsequent 12 months ( P = 0.001). General practice visits also reduced ( P < 0.001). Botulinum toxin injections were administered in 21 patients unresponsive to LR therapy and both general practice and ED/hospital visits declined ( P < 0.001 and P = 0.01, respectively) after injection. Conclusion: A multidisciplinary approach to VCD confers benefit and can be used to allocate appropriate management leading to a reduction in healthcare utilization. Abstract : Multidisciplinary team (MDT) clinics use an integrated approach and individualized services that may benefit vocal cord dysfunction (VCD). We show that a VCD MDT clinic can be used to allocate appropriate management leading to a reduction in healthcare utilization. Watch the video abstract See related Editorial